Depression and anger in fathers of unsettled infants: A community cohort study. (19th September 2016) - Cook, Fallon; Giallo, Rebecca; Petrovic, Zvezdana; Coe, Amy; Seymour, Monique; Cann, Warren; Hiscock, Harriet
Abstract : Aim: To examine the relationship between unsettled infant behaviour and fathers' depressive symptoms, cognitions surrounding infant sleep (anger, doubt), and personal sleep, in a community cohort. Methods: Data were collected from 102 fathers of healthy infants at 4 weeks, 4 months and 6 months of age. Measures included father report of infant sleep and crying problems, depressive symptoms, cognitions about infant sleep and own sleep quality and quantity. Data were analysed using adjusted regression models. Results: Sleep problems at 4 months of age were associated with increased depressive symptoms (adjusted mean difference 2.64 (1.27–4.00)), doubt (adjusted mean difference 1.82 (0.40–3.25)), anger (adjusted mean difference 1.86 (0.51–3.20)), poor personal sleep quantity (adjusted odds ratio (OR) 0.21; 95% confidence interval (CI) 0.09–0.51) and quality (adjusted OR 0.20; 95% CI 0.08–0.51); and at 6 months of age, with increased depressive symptoms (adjusted mean difference 2.56 (1.28–3.84)), anger (adjusted mean difference 1.63 (0.40–2.87)), poor personal sleep quantity (adjusted OR 0.14; 95% CI 0.05–0.38) and quality (adjusted OR 0.28; 95% CI 0.11–0.72). Infant cry problems at 4 months were associated with increased anger (adjusted mean difference 1.98 (0.60–3.36)) and doubt (adjusted mean difference 1.55 (0.05–3.05)); and at 6 months, with increased depressive symptoms (adjusted mean difference 3.04 (1.59–4.69)), anger (adjusted mean difference 2.73 (1.29–4.17)) and less personal sleep (adjusted OR 0.22; 95% CI 0.07–0.71). Conclusion: Fathers of unsettled infants reported greater anger towards their infant and increased depressive symptoms by 4 months infant age, with these symptoms persisting 2 months later. Evidence‐based interventions are needed for these fathers.